2014
DOI: 10.1590/1983-1447.2014.04.44793
|View full text |Cite
|
Sign up to set email alerts
|

Spending with unnecessary complementary tests for hypertension and diabetes in health services

Abstract: The aims of this study were to analyze unnecessary laboratory exams for patients with hypertension and diabetes and to check the expenditures involved. This is an exploratory-descriptive, cross-sectional study with a quantitative approach. We used data from medical records of 293 patients registered in primary units - the Family Health Center (NSF3); secondary: School Health Center (CSE); and tertiary: Hospital das Clínicas (HC) from 2006 to 2009 in a city in Southeastern Brazil. We identified a total of 9,522… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…1 ) ( 8 , 18–109 ), including seven studies for which full texts could not be retrieved, so data were abstracted from the abstract ( 101 , 102 , 104 , 106–109 ). Six included non-English papers were in French, German, Hebrew, Hungarian, Polish and Portuguese, which were translated and assessed by the review team ( 34 , 40 , 110–113 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ) ( 8 , 18–109 ), including seven studies for which full texts could not be retrieved, so data were abstracted from the abstract ( 101 , 102 , 104 , 106–109 ). Six included non-English papers were in French, German, Hebrew, Hungarian, Polish and Portuguese, which were translated and assessed by the review team ( 34 , 40 , 110–113 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most common aim was ‘how does monitoring vary’ ( n = 38), in which studies described the variation in monitoring between regions, patient subgroups or over time. Three studies investigated the costs of over-testing, but none of the studies reported on the possible harms of over-testing to patients ( 34 , 78 , 105 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…"Exames de rotina" em pacientes, a priori sem comorbidades, são grande parte das consultas em atenção básica (LANDSBERG, 2012). Eles geram altos custos em níveis de saúde pública, não se traduzem em melhoria de prevenção doenças e são motivos de transtorno ao paciente e ao médico (ARENA, 2014;TOSCAS, 2015;CAPILHEIRA, 2006).…”
Section: Introductionunclassified